2015
DOI: 10.1590/0104-07072015001080014
|View full text |Cite
|
Sign up to set email alerts
|

Maltrato durante la niñez asociado al uso y abuso de drogas En estudiantes en una universidad de León, Nicaragua

Abstract: Investigación exploratoria que pretendió examinar la asociación entre el maltrato durante la niñez y el uso y abuso de drogas entre los estudiantes de una Universidad en León, Nicaragua. Mediante la aplicación de un cuestionario auto-administrado se obtuvo que el 51.6% de los participantes eran de sexo femenino y el 95.6% se encontraban en las edades de 18 y 24 años. El 22.8% tuvo la percepción de haber sido maltratados durante su infancia. Un 9.0% reportó abuso sexual, en su mayoría del sexo femenino. El 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…Using an adult sample ( n = 34,653), authors examined the association between physical, emotional, and sexual abuse, physical and emotional neglect, and substance use (alcohol, sedatives, opiates, amphetamines, cocaine, amphetamine, cannabis, heroin, hallucinogens, and nicotine), finding that these five types of adverse experiences were associated with an increase in the problematic use in both men and women, except for physical neglect and heroin use in men and emotional neglect and amphetamine and cocaine use in men [ 22 ]. These findings are in line with previous studies that highlight the effect of abuse experiences in childhood, which have been shown to be significantly associated with the use of psychoactive drugs in adult women and men [ 24 ]. In this line of research, the authors studied the link between ACEs and alcohol use in a sample of 7279 subjects, also analyzing the moderating role of psychological stress in men and women [ 25 ].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using an adult sample ( n = 34,653), authors examined the association between physical, emotional, and sexual abuse, physical and emotional neglect, and substance use (alcohol, sedatives, opiates, amphetamines, cocaine, amphetamine, cannabis, heroin, hallucinogens, and nicotine), finding that these five types of adverse experiences were associated with an increase in the problematic use in both men and women, except for physical neglect and heroin use in men and emotional neglect and amphetamine and cocaine use in men [ 22 ]. These findings are in line with previous studies that highlight the effect of abuse experiences in childhood, which have been shown to be significantly associated with the use of psychoactive drugs in adult women and men [ 24 ]. In this line of research, the authors studied the link between ACEs and alcohol use in a sample of 7279 subjects, also analyzing the moderating role of psychological stress in men and women [ 25 ].…”
Section: Introductionsupporting
confidence: 92%
“…These findings are supported by the literature and prior research, which indicate that experiences of physical, emotional, and sexual abuse, as well as neglect and household dysfunctions, are strong predictors of the development of mental health disorders and risk behaviors [ 11 , 42 ]. With respect to substance use problems, as prior research shows, early adversities are associated with a greater vulnerability to emotional dysregulation and problematic use, especially when children experience abuse, household dysfunctions, and violence [ 22 , 24 , 43 ]. This is consistent with the significant associations found in the full sample, regarding experiences of sexual abuse, living with someone with severe mental health problems, bullying, and collective and community violence.…”
Section: Discussionmentioning
confidence: 99%
“…En Latinoamérica se ha empleado la escala ACE en países como Colombia en estudios con niños víctimas de violencia; estos estudios han sido realizados por Jarero, Roque-López, Gómez, y Givaudan [ 19] . Además, Silveira y Abelha [ 18] lo han aplicado en Brasil y en Nicaragua, en tanto que Solórzano et al [ 20] lo utilizó en su estudio orientado a analizar la relación entre trauma infantil y adicciones. En los repositorios digitales de las universidades en Ecuador, se encontró que el cuestionario ACE ha sido empleado en una disertación de pregrado [21].…”
Section: Instrumentosunclassified